“Happiness tree”: a thematic art-based group counseling method for enhancing positive psychological traits in Chinese college students - Xie, Fangzhou; Tang, Mengyao; Wu, Shanshan; Wang, Yong (Frontiers in Psychology, 2025)
IntroductionThis study was a pilot study aimed to evaluate the effectiveness of a new counseling method “Happiness Tree” thematic art-based group counseling.MethodsWe conducted an intervention study in which 36 psychologically healthy college students were instructed to create symbolic tree drawings and engage in reflective writing, helping them identify personal strengths and emotional resources. Students in the experimental group received six online group counseling sessions, while students in the control group received no intervention. Subjective well-being (SWB) and general self-efficacy (GSE) were measured before and after the intervention.ResultsThe results showed that participants in the experimental group experienced preliminary improvements in both SWB and GSE compared to the control group, suggesting potential benefits of the intervention.DiscussionThese findings suggest that the “Happiness Tree” thematic art-based group counseling shows promise for cultivating positive psychological traits in young adults. Our research provides a useful tool for promoting mental health in educational settings.